A nano-photocatalytic self-cleaning composite material and fresh-keeping cover and preparation method thereof
By adding carbon nanotubes and hexagonal boron nitride to the composite material, the problem of uneven dispersion of nanotitanium dioxide in the matrix material is solved, and efficient antibacterial and self-cleaning performance is achieved.
Patent Information
- Application Number
- CN202510107984.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-23
AI Technical Summary
In the prior art, nanotitanium dioxide is difficult to disperse uniformly in the matrix material, limiting the development of self-cleaning composite materials.
By adding carbon nanotubes and hexagonal boron nitride, the dispersion performance of nanotitanium dioxide is improved and its photocatalytic self-cleaning ability is improved. Carbon nanotubes are used as electron conductors and high surface area materials, and boron nitride serves as hole transfer promoters, jointly improving the photocatalytic activity of the material.
The uniform dispersion of antibacterial particles in the composite material is achieved, the antibacterial effect and photocatalytic sterilization ability are improved, and the self-cleaning performance of the composite material is enhanced.
Smart Images

Figure 79IWA03QHIQ4WPKVDX27ACKBTOMM8VQYKVGOQQAO 
Figure XEFRN6PZYAVQL6WZLUFZWZG6QKZCV3AXXPBZ4SSS
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer modification and processing, and particularly relates to a nano photocatalytic self-cleaning composite material and a fresh-keeping cover and a preparation method thereof. Background Art
[0002] With the development of modern industry, people's lives have undergone tremendous changes. On the one hand, life has become more and more convenient, but on the other hand, environmental pollution and deterioration have also brought a lot of troubles to people. People are increasingly concerned about environmental and health issues, and the negative impacts on human health and quality of life caused by the environment have received particular attention. It has gradually become a social consensus to control and control the growth and reproduction of harmful microorganisms, reduce and effectively prevent the impact and harm of harmful microorganisms in the living environment on human life, and reduce the adverse consequences such as pathogen infection, poisoning and disease caused by them. The public's requirements for environmental hygiene in their own residence, work and life have been further improved, which has promoted the rapid development of antibacterial technology and antibacterial materials. Therefore, various antibacterial, environmentally friendly and purification materials have emerged.
[0003] Antimicrobial agents refer to chemical substances that can keep the growth or reproduction of certain microorganisms below the necessary level for a certain period of time. Antibacterial refers to the process of inhibiting the growth, reproduction and survival of bacteria for a certain period of time. The meaning of antibacterial does not mean that microorganisms must be killed. It includes sterilization, disinfection, disinfection and antibacterial. Although some antimicrobial agents can kill microorganisms, most antimicrobial agents only inhibit the growth and proliferation of microorganisms. Usually, the objects of antibacterial are harmful microorganisms that are harmful to human health and bring inconvenience to human life. Antibacterial materials refer to materials that have antibacterial properties and can kill or inhibit the reproduction of bacteria contaminated on the materials for a certain period of time. According to the different antibacterial ingredients, antibacterial agents can generally be divided into three categories: inorganic antibacterial agents, organic antibacterial agents and natural antibacterial agents.
[0004] Semiconductor titanium dioxide has been widely studied and applied at home and abroad due to its stable chemical properties, high photocatalytic activity, strong oxidizability, anti-oxidation and non-toxicity, especially in the field of environmental protection, such as sewage treatment, air purification, self-cleaning and sterilization, providing a very effective method to solve the environmental pollution problems that have long plagued people. In order to further improve the photocatalytic performance of titanium dioxide, its modification technology is developing day by day, such as metal ion doping, nano-titanium dioxide, photosensitization, composite semiconductors and external electric field effects. The modified titanium dioxide semiconductor has higher photocatalytic activity, and is more widely used in the field of environmental protection with better results.
[0005] The inorganic antibacterial materials currently used are mainly ionic antibacterial materials that carry antibacterial ions such as silver, copper, and zinc, and antibacterial materials that utilize photocatalytic activity. The latter have the following characteristics: (1) having both antibacterial and bactericidal effects; (2) rapid antibacterial and bactericidal effects and strong bactericidal power; (3) thorough killing properties; (4) having anti-mildew effects; and (5) multifunctionality, including air purification, sewage treatment, anti-fouling and deodorization, anti-fogging and self-cleaning functions.
[0006] TiO2 can directly utilize ultraviolet light from various sources, including sunlight, to decompose or oxidize various organic or inorganic pollutants at room temperature and remove these pollutants from the air. This technology has the characteristics of low energy consumption, easy operation, and high degree of cleanliness. In particular, it has a more prominent decontamination effect than other methods for some special pollutants, and there is no secondary pollution. It has become a research hotspot in the field of multiphase photocatalysis and has broad application prospects. Since common bacteria and viruses are mainly composed of organic complexes, titanium dioxide can use its strong oxidizing property to kill common bacteria and viruses, and completely degrade them into CO2 and H2O, which plays a role in sterilization, deodorization, anti-fouling, and self-cleaning. However, in the prior art, self-cleaning materials need to add a large amount of nano titanium dioxide, which makes it difficult to disperse it evenly in the matrix material, limiting the development of self-cleaning composite materials. Summary of the invention
[0007] The object of the present invention is to provide a nano-photocatalytic self-cleaning composite material and a fresh-keeping cover and a preparation method thereof, wherein the antibacterial particles are evenly dispersed, the prepared self-cleaning antibacterial composite material has good formability, a broad-spectrum and high-efficiency antibacterial effect, and can better meet the requirements of food, medicine, fruits and vegetables for packaging materials.
[0008] The objective of the present invention is achieved through the following technical solutions:
[0009] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0010] 70-80 parts of aliphatic nylon, 10-20 parts of maleic anhydride graft copolymer, 15-20 parts of nano titanium dioxide, 10-16 parts of carbon nanotubes, 2-4 parts of boron nitride, 1-3 parts of coupling agent, 1-3 parts of release agent, and 0.5-2 parts of antioxidant; the boron nitride is hexagonal boron nitride with a lateral size of 1-5 μm.
[0011] The electron-hole pairs generated in the semiconductor compete with each other in separation / capture and recombination. The smaller the recombination probability of electrons and holes, the higher the photocatalytic activity. The smaller the particle size of semiconductor TiO2, the shorter the time it takes for electrons and holes to migrate to the surface, and the smaller the probability of recombination. At the same time, the smaller the particle size, the larger the specific surface area, which is more conducive to the adsorption of reactants, thereby increasing the reaction probability. Therefore, reducing the particle size of semiconductor TiO2 can significantly improve its catalytic rate. The smaller the TiO2 nanoparticles, the better the effect of killing bacteria, and its photocatalytic sterilization effect can continue to be effective for a period of time after the end of illumination.
[0012] However, nano titanium dioxide, as an inorganic filler, has poor compatibility with the matrix resin and is prone to agglomeration during processing. In order to improve the dispersion performance of nano titanium dioxide and further enhance its photocatalytic self-cleaning ability, the present invention adds a certain amount of carbon nanotubes and hexagonal boron nitride.
[0013] Since carbon nanotubes can conduct electrons and have a high surface area and high adsorption capacity, they are good dopants and carriers for titanium dioxide used as photocatalysts. Carbon nanotubes have a huge electron storage capacity and exhibit metallic conductivity similar to that of metals. Photogenerated electrons in titanium dioxide can move freely to the surface of CNTs, and excess valence band holes in titanium dioxide migrate to the surface and react with adsorbed water or hydroxyl ions to generate active substances, thereby improving the antibacterial activity of titanium dioxide. In addition, CNTs can also act as photosensitizers to transfer electrons to titanium dioxide to improve the photocatalytic activity of titanium dioxide. The two-dimensional layered structural characteristics of hexagonal boron nitride also give it special optical, electrical and chemical properties. As a promoter of hole transfer, the introduction of hexagonal boron nitride can effectively improve the separation and transfer of photogenerated electron-hole pairs in the material, effectively reduce the band gap to improve the visible light absorption of the photocatalyst, and thus enhance the visible light response photocatalytic activity.
[0014] In addition, carbon nanotubes and boron nitride present different physical forms: carbon nanotubes are one-dimensional linear structures, while hexagonal boron nitride presents a graphene-like lamellar structure. The addition of carbon nanotubes and boron nitride can physically improve the dispersion performance of zero-dimensional nano-titanium dioxide, prevent titanium dioxide from agglomerating, and affect its photocatalytic bactericidal performance. Boron nitride is a lamellar structure with a thickness generally below 50nm. By limiting the lateral size of boron nitride to 1μm-5μm, the photocatalytic activity of the composite material can be improved and the antibacterial ability can be improved. When the lateral size of boron nitride is too small, it is difficult to construct a physical isolation network with one-dimensional carbon nanotubes and cannot promote the dispersion of titanium dioxide; when the lateral size of boron nitride is too large, it is not conducive to its own dispersion, and it will also affect the transmittance of light, which is not conducive to the improvement of the self-cleaning ability of the composite material. As a hydrophobic inert filler, the amount of boron nitride should not be too much, otherwise it will easily cause compatibility problems.
[0015] Further, the aliphatic nylon is a mixture of one or more of nylon 6, nylon 66, nylon 56, and nylon 46. Further, the aliphatic nylon is nylon 56. Compared with other aliphatic nylons, nylon 56 has better visible light transmittance and is more conducive to improving the catalytic activity of titanium dioxide. Further, the amount of aliphatic nylon is 72-77 parts, and an appropriate amount of matrix resin can provide sufficient bonding force, so that the inorganic components are bonded to each other, giving the product higher mechanical properties.
[0016] Furthermore, the maleic anhydride grafted copolymer is a mixture of one or more of maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, maleic anhydride grafted ethylene-octene copolymer, and maleic anhydride grafted ethylene propylene diene monomer rubber.
[0017] Further, the nano titanium dioxide is anatase type, and the volume average particle size D50 is 30-100nm. Further, the particle size of titanium dioxide is 60-80nm. Although the smaller the particle size of semiconductor TiO2, the higher the catalytic activity. However, if the particle size is too small, it is easy to cause quantum effect, resulting in a strong agglomeration tendency and difficulty in dispersion; if the particle size is too large, the catalytic activity is reduced.
[0018] Furthermore, the carbon nanotubes are single-walled carbon nanotubes or multi-walled carbon nanotubes.
[0019] Furthermore, the carbon nanotubes are 10-50 μm in length and 20-80 nm in diameter. Furthermore, the amount of carbon nanotubes is 12-14 parts. When the amount of carbon nanotubes is too small, they cannot form a complete isolation network with boron nitride; when the amount is too large, they may agglomerate with each other, which is not conducive to dispersion during the melt processing.
[0020] Furthermore, the coupling agent is a mixture of one or more of KH550, KH560, and KH570.
[0021] Furthermore, the release agent is a mixture of one or more of paraffin wax, stearic acid and its salts, polyethylene wax, and talcum powder; and the antioxidant is a mixture of one or more of phosphite antioxidants or hindered phenol antioxidants.
[0022] On the other hand, the present invention also provides a method for preparing a nano-photocatalytic self-cleaning composite material, comprising the following steps:
[0023] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0024] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0025] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nanometer photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 350-500 rpm; and the extrusion temperature is 260-280°C.
[0026] In addition, the present invention also provides a fresh-keeping cover, which is made of the nano-photocatalytic self-cleaning composite material, and can be specifically prepared by a common injection molding process. The antibacterial particles in the composite material prepared by the present invention are evenly dispersed, and the prepared self-cleaning antibacterial composite material has good formability, a broad spectrum and high efficiency in antibacterial effect, and can better meet the requirements of food, medicine, fruits and vegetables for packaging materials. The composite material is prepared into a fresh-keeping cover, which can produce a strong antibacterial effect and provide long-term antibacterial activity, without the need to spray chemical bactericides, and has a good self-cleaning effect.
[0027] Beneficial effects: The present invention uses nano titanium dioxide as an antibacterial active agent, and adds a certain amount of carbon nanotubes and boron nitride powder to prepare a nano photocatalytic self-cleaning composite material. TiO2 nanoparticles are small and have a better effect in killing bacteria. Its photocatalytic sterilization effect can continue to be effective for a period of time after the end of illumination. In order to improve the dispersion properties of nano titanium dioxide and further improve its photocatalytic self-cleaning ability, the present invention adds a certain amount of carbon nanotubes and hexagonal boron nitride. Carbon nanotubes can conduct electrons and have a high surface area and high adsorption capacity. They are good dopants and carriers for titanium dioxide used as photocatalysts. As a promoter of hole transfer, the introduction of hexagonal boron nitride can effectively improve the separation and transfer of photogenerated electron-hole pairs in the material, effectively reduce the band gap to improve the visible light absorption of the photocatalyst, and thus enhance the visible light response photocatalytic activity. In addition, carbon nanotubes are one-dimensional linear structures, while hexagonal boron nitride presents a graphene-like lamellar structure. The addition of carbon nanotubes and boron nitride can physically improve the dispersion performance of zero-dimensional nano-titanium dioxide, prevent titanium dioxide from agglomerating, and improve its photocatalytic bactericidal performance.
[0028] Other features and advantages of the present invention will be set forth in the following description, and in part will be apparent from the description, or may be learned by practicing the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0032] 70 parts of aliphatic nylon, 10 parts of maleic anhydride grafted copolymer, 15 parts of nano titanium dioxide, 12 parts of carbon nanotubes, 2 parts of boron nitride, 1 part of coupling agent, 1 part of release agent, and 0.5 parts of antioxidant; the boron nitride is hexagonal boron nitride with a lateral size of 1 μm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted polyethylene; the nano titanium dioxide is anatase type with a volume average particle size D50 of 60 nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30 μm and a diameter of 25 nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0033] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0034] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0035] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0036] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0037] Example 2
[0038] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0039] 80 parts of aliphatic nylon, 20 parts of maleic anhydride grafted copolymer, 20 parts of nano titanium dioxide, 14 parts of carbon nanotubes, 4 parts of boron nitride, 3 parts of coupling agent, 3 parts of release agent, and 2 parts of antioxidant; the boron nitride is hexagonal boron nitride with a lateral dimension of 5 μm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted polypropylene; the nano titanium dioxide is anatase type with a volume average particle size D50 of 80 nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30 μm and a diameter of 25 nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0040] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0041] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0042] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0043] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0044] Example 3
[0045] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0046] 70 parts of aliphatic nylon, 20 parts of maleic anhydride grafted copolymer, 15 parts of nano titanium dioxide, 14 parts of carbon nanotubes, 2 parts of boron nitride, 3 parts of coupling agent, 3 parts of release agent, and 0.5 parts of antioxidant; the boron nitride is hexagonal boron nitride with a lateral dimension of 5 μm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted ethylene-octene copolymer; the nano titanium dioxide is anatase type with a volume average particle size D50 of 60 nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30 μm and a diameter of 25 nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0047] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0048] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0049] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0050] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0051] Example 4
[0052] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0053] 72 parts of aliphatic nylon, 13 parts of maleic anhydride grafted copolymer, 16 parts of nano titanium dioxide, 12.5 parts of carbon nanotubes, 2.4 parts of boron nitride, 1.8 parts of coupling agent, 1.9 parts of release agent, and 1 part of antioxidant; the boron nitride is hexagonal boron nitride with a lateral dimension of 3 μm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted ethylene propylene rubber; the nano titanium dioxide is anatase type with a volume average particle size D50 of 70 nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30 μm and a diameter of 25 nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0054] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0055] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0056] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0057] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0058] Example 5
[0059] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0060] 77 parts of aliphatic nylon, 18 parts of maleic anhydride grafted copolymer, 18 parts of nano titanium dioxide, 13.6 parts of carbon nanotubes, 3.5 parts of boron nitride, 2.2 parts of coupling agent, 2.6 parts of release agent, and 1.5 parts of antioxidant; the boron nitride is hexagonal boron nitride with a lateral dimension of 3 μm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted ethylene-octene copolymer; the nano titanium dioxide is anatase type with a volume average particle size D50 of 70 nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30 μm and a diameter of 25 nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0061] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0062] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0063] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0064] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0065] Example 6
[0066] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0067] 75 parts of aliphatic nylon, 15 parts of maleic anhydride grafted copolymer, 17 parts of nano titanium dioxide, 13 parts of carbon nanotubes, 3 parts of boron nitride, 2 parts of coupling agent, 2 parts of release agent, and 1 part of antioxidant; the boron nitride is hexagonal boron nitride with a lateral dimension of 3 μm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted ethylene-octene copolymer; the nano titanium dioxide is anatase type with a volume average particle size D50 of 30 nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30 μm and a diameter of 25 nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0068] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0069] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0070] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0071] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0072] Example 7
[0073] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0074] 75 parts of aliphatic nylon, 15 parts of maleic anhydride grafted copolymer, 17 parts of nano titanium dioxide, 13 parts of carbon nanotubes, 3 parts of boron nitride, 2 parts of coupling agent, 2 parts of release agent, and 1 part of antioxidant; the boron nitride is hexagonal boron nitride with a lateral size of 3μm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted ethylene-octene copolymer; the nano titanium dioxide is anatase type with a volume average particle size D50 of 100nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30μm and a diameter of 25nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0075] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0076] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0077] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0078] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0079] Example 8
[0080] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0081] 75 parts of aliphatic nylon, 15 parts of maleic anhydride grafted copolymer, 17 parts of nano titanium dioxide, 10 parts of carbon nanotubes, 3 parts of boron nitride, 2 parts of coupling agent, 2 parts of release agent, and 1 part of antioxidant; the boron nitride is hexagonal boron nitride with a lateral size of 3μm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted ethylene-octene copolymer; the nano titanium dioxide is anatase type with a volume average particle size D50 of 70nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30μm and a diameter of 25nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0082] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0083] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0084] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0085] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0086] Example 9
[0087] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0088] 75 parts of aliphatic nylon, 15 parts of maleic anhydride grafted copolymer, 17 parts of nano titanium dioxide, 16 parts of carbon nanotubes, 3 parts of boron nitride, 2 parts of coupling agent, 2 parts of release agent, and 1 part of antioxidant; the boron nitride is hexagonal boron nitride with a lateral dimension of 3 μm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted ethylene-octene copolymer; the nano titanium dioxide is anatase type with a volume average particle size D50 of 70 nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30 μm and a diameter of 25 nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0089] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0090] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0091] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0092] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0093] Example 10
[0094] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0095] 75 parts of aliphatic nylon, 15 parts of maleic anhydride grafted copolymer, 17 parts of nano titanium dioxide, 13 parts of carbon nanotubes, 3 parts of boron nitride, 2 parts of coupling agent, 2 parts of release agent, and 1 part of antioxidant; the boron nitride is hexagonal boron nitride with a lateral dimension of 3 μm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted ethylene-octene copolymer; the nano titanium dioxide is anatase type with a volume average particle size D50 of 70 nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30 μm and a diameter of 25 nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0096] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0097] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0098] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0099] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0100] Comparative Example 1
[0101] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0102] 75 parts of aliphatic nylon, 15 parts of maleic anhydride grafted copolymer, 17 parts of nano titanium dioxide, 16 parts of carbon nanotubes, 0 parts of boron nitride, 2 parts of coupling agent, 2 parts of release agent, and 1 part of antioxidant; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted ethylene-octene copolymer; the nano titanium dioxide is anatase type, and the volume average particle size D50 is 70nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30μm and a diameter of 25nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0103] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0104] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, coupling agent, release agent, and antioxidant according to weight proportions;
[0105] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0106] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0107] Comparative Example 2
[0108] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0109] 75 parts of aliphatic nylon, 15 parts of maleic anhydride grafted copolymer, 17 parts of nano titanium dioxide, 0 parts of carbon nanotubes, 16 parts of boron nitride, 2 parts of coupling agent, 2 parts of release agent, and 1 part of antioxidant; the boron nitride is hexagonal boron nitride with a lateral size of 3 μm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted ethylene-octene copolymer; the nano titanium dioxide is anatase type with a volume average particle size D50 of 70 nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0110] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0111] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0112] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0113] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0114] Comparative Example 3
[0115] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0116] 75 parts of aliphatic nylon, 15 parts of maleic anhydride grafted copolymer, 17 parts of nano titanium dioxide, 13 parts of carbon nanotubes, 3 parts of boron nitride, 2 parts of coupling agent, 2 parts of release agent, and 1 part of antioxidant; the boron nitride is hexagonal boron nitride with a lateral dimension of 500nm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted ethylene-octene copolymer; the nano titanium dioxide is anatase type with a volume average particle size D50 of 70nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30μm and a diameter of 25nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0117] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0118] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0119] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0120] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0121] Comparative Example 4
[0122] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0123] 75 parts of aliphatic nylon, 15 parts of maleic anhydride grafted copolymer, 17 parts of nano titanium dioxide, 13 parts of carbon nanotubes, 3 parts of boron nitride, 2 parts of coupling agent, 2 parts of release agent, and 1 part of antioxidant; the boron nitride is hexagonal boron nitride with a lateral dimension of 8 μm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted ethylene-octene copolymer; the nano titanium dioxide is anatase type with a volume average particle size D50 of 70 nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30 μm and a diameter of 25 nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0124] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0125] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0126] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0127] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0128] Comparative Example 5
[0129] A nano-photocatalytic self-cleaning composite material comprises the following components in parts by weight:
[0130] 75 parts of aliphatic nylon, 15 parts of maleic anhydride grafted copolymer, 17 parts of nano titanium dioxide, 13 parts of carbon nanotubes, 6 parts of boron nitride, 2 parts of coupling agent, 2 parts of release agent, and 1 part of antioxidant; the boron nitride is hexagonal boron nitride with a lateral size of 3μm; the aliphatic nylon is nylon 56; the maleic anhydride grafted copolymer is maleic anhydride grafted ethylene-octene copolymer; the nano titanium dioxide is anatase type with a volume average particle size D50 of 70nm; the carbon nanotubes are multi-walled carbon nanotubes; the multi-walled carbon nanotubes have an average length of 30μm and a diameter of 25nm; the coupling agent is KH550; the release agent is paraffin; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;
[0131] A method for preparing a nano-photocatalytic self-cleaning composite material comprises the following steps:
[0132] S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions;
[0133] S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix;
[0134] S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nano-photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 400 rpm; and the extrusion temperature is 272°C.
[0135] Performance testing: The nano-photocatalytic self-cleaning composite materials prepared in Examples 1-10 and Comparative Examples 1-5 were injection molded into standard samples, and the tensile strength (referenced to ISO 527-2), notched impact strength (referenced to ISO 179), and antibacterial properties (referenced to GB / T21510-2008) of the samples were tested. The test results are shown in Tables 1-2 below.
[0136]
[0137]
[0138] As can be seen from Table 1-Table 2, the present invention uses nano titanium dioxide as an antibacterial active agent, and adds a certain amount of carbon nanotubes and boron nitride powder to prepare a nano photocatalytic self-cleaning composite material. TiO2 nanoparticles are small and have a good effect on killing bacteria. Its photocatalytic sterilization effect can continue to be effective for a period of time after the end of illumination. In order to improve the dispersibility of nano titanium dioxide and further improve its photocatalytic self-cleaning ability, the present invention adds a certain amount of carbon nanotubes and hexagonal boron nitride. Carbon nanotubes can conduct electrons and have a high surface area and high adsorption capacity. They are good dopants and carriers for titanium dioxide used as photocatalysts. As a promoter of hole transfer, the introduction of hexagonal boron nitride can effectively improve the separation and transfer of photogenerated electron-hole pairs in the material, effectively reduce the band gap to improve the visible light absorption of the photocatalyst, thereby enhancing the visible light response photocatalytic activity. In addition, carbon nanotubes are one-dimensional linear structures, while hexagonal boron nitride presents a graphene-like lamellar structure. The addition of carbon nanotubes and boron nitride can physically improve the dispersion performance of nano titanium dioxide with zero-dimensional structure, prevent titanium dioxide from agglomerating, improve its photocatalytic bactericidal performance, prevent the formation of colonies on the surface of the product, and give it self-cleaning performance. Specifically, compared with Example 10, Comparative Examples 1 and 2 lack boron nitride or carbon nanotubes, respectively, and cannot improve the light absorption performance and charge transfer ability of titanium dioxide, and the antibacterial ability is deteriorated; and the dispersion performance of nano titanium dioxide with zero-dimensional structure cannot be improved physically, resulting in reduced mechanical properties of the composite material. Comparative Examples 3-5 show that boron nitride is a lamellar structure. By limiting the lateral size of boron nitride to 1μm-5μm, the photocatalytic activity of the composite material can be improved and the antibacterial ability can be improved. When the lateral size of boron nitride is too small, it is difficult to construct a physical isolation network with one-dimensional carbon nanotubes, and it is impossible to promote the dispersion of titanium dioxide; when the lateral size of boron nitride is too large, it is not conducive to its own dispersion, and it will also affect the transmittance of light, which is not conducive to the improvement of the self-cleaning ability of the composite material. Moreover, as a hydrophobic inert filler, the amount of boron nitride cannot be too much, otherwise it will easily cause compatibility problems.
[0139] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A nano-photocatalytic self-cleaning composite material, characterized in that: Contains the following components in parts by weight: 70-80 parts of aliphatic nylon, 10-20 parts of maleic anhydride graft copolymer, 15-20 parts of nano titanium dioxide, 10-16 parts of carbon nanotubes, 2-4 parts of boron nitride, 1-3 parts of coupling agent, 1-3 parts of release agent, and 0.5-2 parts of antioxidant; the boron nitride is hexagonal boron nitride with a lateral size of 1-5 μm; The nano titanium dioxide is anatase-type, and the volume average particle size D50 is 30-100 nm; The carbon nanotubes have a length of 10-50 μm and a diameter of 20-80 nm.
2. A nano-photocatalytic self-cleaning composite material as claimed in claim 1, characterized in that: The aliphatic nylon is a mixture of one or more of nylon 6, nylon 66, nylon 56 and nylon 46.
3. A nano-photocatalytic self-cleaning composite material as claimed in claim 1, characterized in that: The maleic anhydride grafted copolymer is a mixture of one or more of maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, maleic anhydride grafted ethylene-octene copolymer, and maleic anhydride grafted ethylene propylene diene monomer rubber.
4. A nano-photocatalytic self-cleaning composite material as claimed in claim 1, characterized in that: The carbon nanotubes are single-walled carbon nanotubes or multi-walled carbon nanotubes.
5. A nano-photocatalytic self-cleaning composite material as claimed in claim 1, characterized in that: The coupling agent is a mixture of one or more of KH550, KH560 and KH570.
6. A nano-photocatalytic self-cleaning composite material as claimed in claim 1, characterized in that: The release agent is a mixture of one or more of paraffin wax, stearic acid and its salt, polyethylene wax, and talcum powder; the antioxidant is a mixture of one or more of phosphite antioxidants or hindered phenol antioxidants.
7. The method for preparing a nano-photocatalytic self-cleaning composite material according to claim 1, characterized in that: The following steps are involved: S1. Weigh aliphatic nylon, maleic anhydride graft copolymer, nano titanium dioxide, carbon nanotubes, boron nitride, coupling agent, release agent, and antioxidant according to weight proportions; S2, adding all the materials in step S1 into a high-speed mixer and mixing them evenly to obtain a premix; S3, adding the premix obtained in step S2 into a twin-screw extruder, and performing melt blending and extrusion to obtain a nanometer photocatalytic self-cleaning composite material; wherein the screw speed of the twin-screw extruder is 350-500 rpm; and the extrusion temperature is 260-280°C.
8. A fresh-keeping cover, characterized in that: It is made from the nano-photocatalytic self-cleaning composite material described in any one of claims 1 to 6.
Citation Information
Patent Citations
Wear-resistant antibacterial conductive nylon and preparation method thereof
CN112409782A